The scholarship of learning modern languages and cultures: integrating education, research and human development - Vera López, Hortensia Beatriz (2012)
By taking learning as the axis of scholarship, personal and social epistemologies have a common ground: experience and reflective action. I am not considering learning as a vehicle whose success is measured to the extent that a portion of the external world is appropriated, but as a qualitatively different way to see, understand and handle experience. A scholarship of learning is tightly bound to the experiential roots of objects of study that keep on changing in individual and collective histories. Therefore, a scholarship of learning is not a set of context-free skills but a complex process of transformation of its practitioners’ identity and agency over themselves and their object of study. Such two-fold construction orientates a discipline no less than the ways of knowing, acting and being of those engaged in its investigation. I propose that the object of study of Modern Languages and Cultures should be literacy in the multilayered symbolic codes (some of which are tacit) that make intercultural interchanges intelligible and effective. The scope of this dissertation, however, is restricted to the investigation of deep learning in literacy. My thesis is that Modern Languages and Cultures should not be limited to objects of study, such as language, discourse, texts, films, etc. but has to include the processes of agentification of the learner and making sense of his or her experience in a foreign language and culture. I advocate the investigation of the experiential roots of language and culture in a scholarship of learning which seeks to integrate research and education, on the one hand, and language and content, on the other. Experience and learning are subjective-objective processes, and so I advise the epistemological revaluation of subjectivity. I propose that subjectification (i.e. the construction of the subject) is not only relevant for human development and social well-being, but is a source of knowledge in the Humanities.